Caribbean international relations beyond 1992: between Europe and North America - Payne, Anthony ([West Indian Commission] [St. Michael]BB, 1991)
Considers the implications and possibilities for CARICOM of relations with the European Community in the context of the Single Market, NAFTA and other trading arrangements impacting on CARICOM. Identifies diplomacy as the single most important resource which the region can use to advance its interests, focussing on options open to the Commonwealth Caribbean within Europe and North America.